2007
DOI: 10.1002/jcb.21388
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol attenuates MCP‐1 and MMP‐9 expression in vivo in LPS‐administrated balloon‐injured rabbit aorta and in vitro in LPS‐treated monocytic THP‐1 cells

Abstract: Monocyte chemoattractant protein-1 (MCP-1) and matrix metalloproteinase-9 (MMP-9) are involved in vascular inflammation. We tested the hypothesis, and explored the underlining mechanisms that cilostazol, a phosphodiesterase 3 inhibitor with antiplatelet and antithrombotic properties, inhibits lipopolysaccharide (LPS)-induced MCP-1 and MMP-9 expression. In a rabbit aorta balloon-injury model, administration of LPS increased macrophage infiltration and MCP-1 and MMP-9 expression; cilostazol supplementation preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Therefore, various efforts to design treatment strategies for sepsis have been focused on the elimination of the potentially detrimental pro-inflammatory mediators. It is well known that cilostazol increases intracellular cAMP levels by blocking its hydrolysis by PDE 3, resulting in suppressed inflammation [21]. We hypothesized that anti-inflammatory effects of cilostazol for the treatment of septic shock were via an increased intracellular cAMP level.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, various efforts to design treatment strategies for sepsis have been focused on the elimination of the potentially detrimental pro-inflammatory mediators. It is well known that cilostazol increases intracellular cAMP levels by blocking its hydrolysis by PDE 3, resulting in suppressed inflammation [21]. We hypothesized that anti-inflammatory effects of cilostazol for the treatment of septic shock were via an increased intracellular cAMP level.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with a previous study demonstrating that cilostazol decreased MMP-9 expression in balloon-injured vasculature. 48 Cilostazol is known to raise the intracellular cAMP concentration in endothelial cells. In this context, cAMP promotes functional integrity of tight junctions between endothelial cells in the blood-brain barrier.…”
Section: Kasahara Et Al Cilostazol and Tpa-induced Hemorrhage 503mentioning
confidence: 99%
“…Cilostazol functions as a platelet aggregation inhibitor (15) and vasodilator (16), and is mainly used for treating patients with peripheral arterial disease (17) and intermittent claudication (18). In addition, it seems to reduce inflammation and inhibit MMP expression by increasing AMP and inhibiting the p38/ JNK pathway (19). Previous studies have demonstrated that cilostazol inhibits apoptosis under several circumstances (12,(20)(21)(22).…”
Section: Conclusion Our Findings Indicate That Cilostazol Prevents Nmentioning
confidence: 99%